LPS‐mediated septic shock is augmented in ceramide synthase 2 null mice due to elevated activity of TNFα‐converting enzyme. Issue 17 (13th July 2015) - Ali, Mohammad; Saroha, Ashish; Pewzner-Jung, Yael; Futerman, Anthony H.
Abstract : Tumor necrosis factor α (TNFα) is an inflammatory cytokine that plays an intimate role in septic shock. Injection of high levels of lipopolysaccharide induces septic shock and death in mice within 30 h, whereas ceramide synthase 2 (CerS2) null mice, defective in the synthesis of very‐long acyl chain ceramides, die within ∼10 h. The augmented rate of death of CerS2 null mice is due to elevated levels of TNFα secretion as a result of enhanced activity of TNFα‐converting enzyme (TACE). We discuss the relationship between the sphingolipid acyl chain length and TACE activity and the relevance of this data to septic shock. Abstract : Ceramide synthase 2 (CerS2) null mice are unable to synthesize very‐long acyl chain ceramides. CerS2 null mice show a number of pathologies in the liver due to alterations of specific biochemical pathways. We now show that CerS2 null mice are hypersensitive to LPS‐mediated sepsis due to elevated TNFα secretion. Elevated TNFα secretion was due to elevated TACE activity in both hepatocytes and macrophages.